Objective evaluation of vertical Z-plasty with double transposition vermillion flaps for secondary whistling deformity correction: A method for uni- and bilateral correction. Issue 10 (October 2019) - Scheller, Konstanze; Bolz, Julia; Scheller, Christian; Haase, Roland
Abstract: Objectives: This study describes a modified method for secondary correction of whistling deformities in patients with unilateral and bilateral cleft lip/palate (CL/P), using a horizontal double transposition vermilion flap, including parts of the orbicularis oris muscle. The pre- and postoperative results were objectively evaluated. Study design: 34 patients with a whistling deformity who underwent secondary reconstruction between 07/2013 and 11/2018 were included in this study (mean age 20.2 ± 11.6 years). 24 patients were male and 10 female. 30 patients presented with cleft lip and palate (CLP) — 15 bilateral, nine on the left side and six on the right. Four patients had only a left-side cleft lip (CL). The whistling deformity reconstruction was carried out using two triangular transposition vermilion flaps with muscle parts, for a vertical Z-plasty. The surgical procedure is normally performed under local anesthesia in all patients older than 10 years. For statistical evaluation, the size of the whistling defect in the vermilion was determined on photographs before and 6–9 months after surgery. The individual defect score (DS) was evaluated pre- and postoperatively. In all patients, no additional surgical procedures, such as rhinoplasty or scar correction in the upper lip, were carried out simultaneously. Results: Minor (DS < 400), moderate (DS 400–1400), and severe (DS > 1400) whistling defects were surgically corrected. The whistling defect score was significantly reduced in all patient groups (p < 0.001). In six patients the result of surgery was rated as 'acceptable' (DS > 30), in five patients as 'good' (DS 10–30), and in 23 patients as 'very good' (DS 0–10). Conclusions: This study describes a modified method for whistling deformity reconstruction in uni- and bilateral clefts. The aesthetic results are based on a reconstruction of the subcutaneous muscle layers and the creation of a symmetrical lip contour and prolabium using transposition flaps from the lateral side of the cleft. The great advantage is the uncomplicated performance under local anesthesia, even for all children over 10 years, and the short operation time. Postoperative complications did not occur.